Influence of varying Germanium content on the optical function dispersion of Fe 2MnSi xGe 1-x: An ab initio study - Ali Hussain, Reshak, Prof. Dr.; Charifi, Zoulikha; Baaziz, Hakim (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/